Comparison of Quality of Life Using Chronic Venous Insufficiency Questionnaire (CIVIQ) and Factors Affecting It in Chronic Venous Insufficiency Patients After Endovenous Microwave Ablation with High Ligation + Stripping - Hudaya, Miradz; Pratama, Dedy; Sanyoto, Dhanasari Vidiawati (Jurnal Locus Penelitian dan Pengabdian, 2025)
The prevalence of Chronic Venous Insufficiency (CVI) continues to increase globally, with approximately 30-40% of the adult population experiencing varicose veins as an early manifestation of venous insufficiency. To date, there are few studies that compare endovenous microwave ablation (EMA) with conventional management of high ligation and stripping (HLS) in terms of quality of life in CVI patients. This study aimed to assess the difference in quality of life of post-operative CVI patients using the CIVIQ-20 questionnaire, by comparing patients who were treated with EMA versus HLS. This prospective cohort study involved 40 CVI patients from RSCM, Hermina Bekasi Hospital, and Hermina Depok Hospital in the May-June 2025 period. Data was collected using questionnaires. Bivariate analysis with Chi-Square test, Fischer's exact test, Independent T-test, and Mann-Whitney U test. Overall, the mean change (?) of CIVIQ score for EMA vs. HLS was 12.82 ± 6.97 vs. 14.33 ± 6.78 (p = 0.334). In patients ? 60 years of age, the ? CIVIQ score for HLS vs. EMA was 16.17 ± 5.67 vs. 10.89 ± 2.67 (p = 0.029). In female patients, the ? CIVIQ score for HLS vs. EMA was 16.63 ± 5.32 vs. 10.23 ± 4.21 (p = 0.006). No significant difference in ? CIVIQ score between HLS and EMA was found in patients < 60 years of age, male, or patients with obesity compared to normoweight. In 60?year-old CVI patients and female CVI patients, management with HLS resulted in a significantly higher CIVIQ-20 ? score than EMA. This showed a better quality of life in both groups of patients when treated with HLS.